2011
DOI: 10.1590/s1517-86922011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação funcional da nocicepção do joelho de ratos tratada com laser de baixa potência e natação

Abstract: This study aimed at evaluating and comparing the effects of low-level laser therapy (LLLT) and a forced swimming training in a joint nociception model on Wistar rats, in order to functionally register pain by observation of paw elevation time (PET) during gait on a metal cylinder. Thirty-two Wistar rats were divided into four groups: CG -untreated animals submitted to nociception induction on right knee; LG -nociception and treated with 670 nm and 8 J/cm2 LLLT; SG -nociception and swimming for 10 minutes in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(3 reference statements)
1
3
0
3
Order By: Relevance
“…Laser effects are dosedependent and the expected response is not obtained with it is used in under or overdoses; however, in adequate doses there is effective analgesic effect 11,12 , in spite of a huge discrepancy with regard to adequate dose and wavelength 13 , thus raising the need for other studies to evaluate such dosimetric parameters. Our study has observed that the dose used (8 j/cm 2 ) with 820 nm laser was adequate to induce analgesia as already observed by other study 1 . The evaluation tool used is also referenced in the literature, showing that animals with increased nociception have longer time for flinching while ambulating for one minute, as compared to animals without painful stimulation 14 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Laser effects are dosedependent and the expected response is not obtained with it is used in under or overdoses; however, in adequate doses there is effective analgesic effect 11,12 , in spite of a huge discrepancy with regard to adequate dose and wavelength 13 , thus raising the need for other studies to evaluate such dosimetric parameters. Our study has observed that the dose used (8 j/cm 2 ) with 820 nm laser was adequate to induce analgesia as already observed by other study 1 . The evaluation tool used is also referenced in the literature, showing that animals with increased nociception have longer time for flinching while ambulating for one minute, as compared to animals without painful stimulation 14 .…”
Section: Resultssupporting
confidence: 89%
“…Pain may be associated to real or potential tissue injury and may cause incapacity by decreasing injured tissue function due to structural injury and tissue edema 1,2 . Low power laser is widely used in therapies especially aiming at decreasing pain 1 and repairing tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there was the formation of an edema in all of the groups after the injury and that for the treated groups there was a decrease in the edema. Demonstrating that the treatment with low level laser led to a reduction in the edema of the animals with tendinae trauma 17 . That confirms the findings of our research, in which a similar methodology was applied and there was also a decrease of pain with the usage of the low level laser.…”
mentioning
confidence: 98%
“…A esse estresse também pode ser creditado o efeito analgésico do exercício [16]. Apesar de haver grande semelhança fisiológica, celular e molecular entre os modelos animais e humanos, existem limitações no uso de animais, e a extrapolação de resultados de modelos para humanos deve ser realizada com cautela.…”
Section: Discussionunclassified
“…Ainda, possui ações anti-inflamatórias por ativação imune, que culminam em eventos antidepressivos [14,15]. Contudo, em animais submetidos a modelo experimental agudo de dor articular em joelhos, a natação por 10 minutos não produziu diminuição do quadro álgico [16], provavelmente por causa da pequena duração e intensidade do exercício, visto que, segundo Koltyn e Umeda [17], a hipoalgesia parece ocorrer quando o exercício é realizado em altas intensidades. Ainda, observaram, em camundongos, que a corrida voluntária em esteira gerou aumento na ansiedade, avaliado pelo teste de campo aberto, labirinto elevado e caixa claro/escuro, além de altos níveis de corticosterona nas fezes dos animais [18].…”
Section: Introductionunclassified